La rapide création du Parc Naturel marin de Mayotte - Nicolas Legoff (EchoGéo)
The 2nd french Marine Protected Area was officially created in Mayotte in January 2010, thanks both to a swift procedure and to a strong determined policy. It clearly shows the will of France to manage a broad area in south-west of the Indian Ocean even if its means of action are still to settle. Beyond environemental protection, the park is seen as a useful tool for an island still considered as emergent. From fishing to tourism, many activities hope to take advantage from the dynamic set in motion.